Use of ICT in Higher Education in India - Bhavna Dubey and Dr. Sita Devi (International journal of economic perspectives, 2022)
Higher education has been one of the key sectors, which provide direction to the national development. In the new millennium, higher education receives greater priority in the national development and efforts are being made to enlarge the educational network of the colleges, universities and institutions of national importance along with the strengthening of the staff, faculty and infrastructure for quality education. The increasing use of information and communication technologies has brought changes to teaching and learning at all levels of higher education systems to improve the quality.